Normative profiles for serve speed for the training of the serve and reception in volleyball - Palao, J. M.; Valadés, D. (The Sport Journal, 2014)
The objectives of the present study were: a) to assess normative profiles for the serve speed of peak-performance volleyball players in order to guide practice sessions for men´s teams (study 1) and women´s teams (study 2), and b) to establish the possibilities and the ranges of speed that a volleyball throwing machine can offer for working on reception in volleyball (study 3). In studies 1 and 2, the serve techniques and the maximal speeds were analysed in men´s (2097 serves) and women´s (2056 serves) volleyball. Study 3 consisted of analysing the release speeds of the ball that are generated from the various speed settings that can be programmed with the throwing machine. The results provide normative profiles for the ranges of speed of the different types of serve for both men´s and women´s volleyball. Additionally, they indicate the speeds that a volleyball throwing machine provides for reception training in volleyball.